Effects of Plant Spacing and Mulching on Yield and Profitability of Lettuce (Lactuca sativa L.) - Moniruzzaman, M (Journal of Agriculture & Rural Development, 2008)
A field experiment with three levels of spacing (40 x 20 cm, 40 x 30 cm and 40 x 40 cm) and two levels of mulching (mulch and non-mulch) was conducted to find out the effect of plant spacing and mulching on yield and profitability of lettuce cv. Green Wave at the Agricultural Research Station, Raikhali, Rangamati Hill District for the two consecutive years during 1999-00 and 2000-01. Plant spacing, mulching and their interaction showed significant effect on yield and yield components of lettuce. The highest fresh yield of lettuce was obtained from the closest spacing (40 x 20 cm) that was statistically similar to that recorded of medium spacing (40 x 30 cm) during both the years. Significantly higher fresh yield of lettuce was obtained from the mulched plants than that of unmulched plants. The highest yield (25.9 t/ha in 1999-00 and 28.3 t/ha in 2000-01 with an average of 27.10 t/ha) was observed in the spacing of 40 x 20 cm with mulch, which was statistically at par with the spacing of 40 x 30 cm with mulch. The results also revealed that higher Gross Return (Tk. 216, 800.00) was obtained from the closest spacing in combination with mulch followed by medium spacing (40 x 30 cm) with mulch (Tk. 210, 160.00). The treatment combination of 40 x 30 cm spacing and mulching gave the highest benefit cost ratio (8.84). But the benefit cost ratio (4.22) from the treatment combination of 40 x 20 cm spacing and mulching was less due to the involvement of higher seedling cost. Key words: Spacing, mulching, lettuce, yield, profitability.